PENGGUNAAN LEARNING RESOURCES DALAM PROSES PEMBELAJARAN AGAMA ISLAM - Saeful Anam; Arina Almasal Firdaus (JP : JURNAL PENDIDIKAN, 2020)
Abstract: This study aims to know the use of the learning environment as a learning resource that supports Islamic learning in SMK 2 Bojonegoro. This research is a field research with a qualitative approach. The technique used in data analysis is an interactive model that includes data collection, data reduction, data display and conclusion drawing. The results showed that the environment used as a source of learning at SMK Negeri 2 Bojonegoro included the environment around the school, both the natural, social, or cultural environment. This proves that the use of the environ-ment as a source of learning is one solution to the problems of the existing religious learning process. With the use of the environment, students do not only learn about concepts, but also practice in practicing the values of religious teachings to be able to know the details of the process of religious social interaction.Keywords: learning environment, Islamic Education